PENGARUH LEVERAGE, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS: Perusahaan Industri Makanan dan Minuman di Bursa Efek Indonesia selama periode 2017 – 2019. - Neny Kusumadewi (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2022)
Companies with good performance will be able to achieve the goals to be achieved by the company, which is to maximize the value of the company. That goals can be achieved by increasing the probability of the company. This research is conducted as a mean to test influence of leverage, sales growth and company size to profitability of the Food and Beverege industry company in Indonesian during priod 2017-2019. The date used is sekondary data using method and number of population as many as 18 companies, research sampel taken on sampling purposive basis. Criterion of sampel fulfilling counted 11 companies. Analysis technique using panel data regretion with using Eviews 9.0 program to get an overview that includes the relationship between one variable with another variable. Result of analysis prove that by parsial variable of leverage significant effect on profitability, sales growth no significant effect on profitability, size significant on profitability.